Phosphorothioate analogs of oligodeoxynucleotides: inhibitors of replication and cytopathic effects of human immunodeficiency virus. - Matsukura, M (1987)
Nuclease-resistant phosphorothioate analogs of certain oligodeoxynucleotides have been tested in vitro as antiviral agents against human immunodeficiency virus (HIV) in human T cells. Phosphorothioate analogs complementary to HIV sequences, as well as noncomplementary analogs including homooligomers, exhibited potent antiviral activity. The antiviral activity was related to the base composition of the analogs, and longer phosphorothioates were more effective than shorter ones. A 28-mer phosphorothioate oligodeoxycytidine (S-dC28) at a concentration of 1 microM exhibited potent antiviral activity and inhibited de novo viral DNA synthesis as shown by Southern blot analysis. However, S-dC28 failed to inhibit gag expression in chronically infected T cells assessed by immunofluorescent assay at concentrations up to 25 microM. An N3-methylthymidine-containing phosphorothioate analog, which does not hybridize efficiently in vitro to complementary normal DNA, showed no antiviral activity. A 14-mer phosphorothioate oligodeoxycytidine (S-dC14) synergistically enhanced the antiviral activity of 2',3'-dideoxyadenosine, an anti-HIV nucleoside. Therefore, phosphorothioate analogs of oligodeoxynucleotides could represent a unique class of experimental therapeutic agents against the acquired immunodeficiency syndrome and related diseases. However, their mechanism of action is likely to be complex.